1997
DOI: 10.1287/orsc.8.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Perspective—The Black Box of Organizational Demography

Abstract: Since its definition in the early 1980s, organizational demography has become an influential research area. Scholars map the relationship between demographic variables and organizational outcomes, examining such questions as whether increasing work group diversity leads to greater turnover and whether decreasing tenure similarity within a top management team leads to more numerous strategic reorientations. Asking such questions requires only a demographic predictor and an outcome, but answering them often requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
593
0
23

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 712 publications
(628 citation statements)
references
References 54 publications
12
593
0
23
Order By: Relevance
“…We attempt to take one step toward eliminating the treatment of gender as a ''black box." Studying demographic variables as black boxes (without insight into their underlying psychological constructs) allows for prediction, but it eliminates explanation, obscuring clear thinking (Lawrence, 1997). Our findings suggest that gender is a proxy for moral identity, which predicts unethical behavior under certain circumstances.…”
Section: Theoretical Contributionsmentioning
confidence: 85%
“…We attempt to take one step toward eliminating the treatment of gender as a ''black box." Studying demographic variables as black boxes (without insight into their underlying psychological constructs) allows for prediction, but it eliminates explanation, obscuring clear thinking (Lawrence, 1997). Our findings suggest that gender is a proxy for moral identity, which predicts unethical behavior under certain circumstances.…”
Section: Theoretical Contributionsmentioning
confidence: 85%
“…According to this perspective, as demographic diversity increases so do the group's cognitive resources and the ability to engage in more complex and innovative problem-solving (Bantel & Jackson, 1989;Jackson & Ruderman, 1995;Watson et al, 1993). However, other researchers have noted that demographic characteristics do not covary perfectly with these underlying psychological attributes (Bantel & Jackson, 1989;Hambrick & Mason, 1984), and that the link between demographic and cognitive diversity may be more complex than generally assumed (Kilduff et al, 2000;Lawrence, 1997). For this reason, this study tested the possible effects of both cognitive and demographic diversity in work teams simultaneously.…”
Section: General Findings From the Group Diversity Literaturementioning
confidence: 99%
“…The degrees to which demographic individual differences are task relevant (e.g., functional background) are proposed to be important for the potency of diversity effects (Lawrence, 1997;Harrison, Price, & Bell, 1998). Indeed, several meta-analyses have demonstrated that the nature of the team's task accounts for the fluctuating impact of individual heterogeneity in teams (Bell, 2007;Bowers, Pharmer, & Salas, 2000;Stewart, 2006).…”
Section: Designing For Diversitymentioning
confidence: 99%